Factors affecting Singapore investors when making investment decisions in China. - Choo, Joon Yong. (2009)
Singapore's regionalisation drive which began in the early '90s is starting to see results. According to the Economie Development Board, Singapore firms' investment in the region exceeds S$11b.1 China, predicted by some economists to have the potential to become the most powerful economie nation in the world, is a popular investment destination for Singapore's investors. According to a EDB report2, Singapore is the fifth largest investor in China for last two consecutive years.